BLIND TEST PERBANDINGAN PERFORMA SEMEN POWERMAX DENGAN SEMEN PCC+ BERDASARKAN DATA SERTA PERSEPSI PEKERJA DAN PELAKU KONSTRUKSI DI LAPANGAN - Febi Rianda (Departement of Civil Engineering, Universitas Winaya Mukti, 2023)
Cement is known as an adhesive material used to bonding building materials or other materials. Portland cement is a construction material that used in the production of concrete. This study is a blind test on Powermax cement and Powermax's replacement product, PCC+. Powermax is known as cement which has several superior characteristics, Powermax has a good flow and no need a lot of water but still produces fluffier and maximum mix. PCC+ cement is a hydraulic cement made from grinding Portland cement slag with gypsum and pozzolanic materials with one or more inorganic materials. This study used 3 locations with different research objects, consists of CPM Sampono Cimahi (Concrete Panel, U-Ditch, and Box Culvert), Central Cimahi (Mock Up Column (internal)), and CPM Samson Jaya Tasikmalaya (Paving Block). The results showed that Powermax has a darker color than PCC+ viewed by color and visuals. PCC+ is already at the bleeding point with 70% w/c while Powermax with 70% w/c is still sufficient for concrete quality > K-200 from the builder's perception viewed by water requirements. PCC+ has a compressive strength of 10% stronger than Powermax viewed by the resulting compressive strength,. This study is useful to help readers know the performance between Powermax and PCC+ as a consideration in selecting the type of cement to plan construction projects.